Proyecto de factibilidad para la creación de una empresa proveedora de internet domiciliario y corporativo en la ciudad de Saraguro, provincia de Loja - Cango Quizhpe, Lourdes Beatriz (2016)
This research was conducted in the City of Saraguro, aiming to present a proposal to implement a supplier of Internet in the town of Saraguro. Among the objectives to be raised they are: Perform market research for analysis of supply and demand in it; Conduct a technical study to determine what the optimal location, to determine the size and project engineering, as well as the functional organizational structure of the company; Conduct a financial study in order to determine the budget, expenses and revenues arising from it; Assess the financial viability assessment made by indicators such as net present value (NPV), Internal Rate of Return (IRR), benefit cost ratio (R / BC), capital recovery period (PRC) and sensitivity analysis to determine the feasibility of the project. With regard to the methods used are taken into account, the deductive method to collect the information used in the literature review and allowed a broad overview regarding the provision of internet, the inductive method which was the basis role in the implementation of those surveys which yielded information for market research. A study of merado, whose information was obtained by applying a survey of a sample population of 290 families in the City of Saraguro and an interview was conducted at 2 suppliers. In the study of market supply and demand which allowed determine the unmet demand for facilities that generate 216 2,586 internet services was analyzed. 5 With this information the technical study where the size of the company where the installed capacity of 2,220 services and capacity utilization 1700 manifests detailing services performed, plus the location will be at the Gold Street between Loja and Jose Maria was determined Vivar, project engineering, infrastructure, process for service delivery and organizational structure where the company is legally incorporated as a limited company was also established. The financial study which determined that the implementation of this project a capital of 19,882.68, of which 47.85% of the investment relates to the contributions of partners and 25.15% required is then performed funds in the National Development Bank in the City of Saraguro. In addition, production costs and sales prices that will govern settled, the profit and loss account to have insight into the possible uses for partners presented; while the point of balance that will enable the company Lahore without causing a loss is determined. Finally, the financial evaluation was performed to establish the suitability of the project and its implementation for which the following indicators were analyzed: Net Present Value with a favorable outcome of $ 6,612.12; Internal Rate of Return of 19.17% which well exceeds expectations; Benefit Cost Ratio is $ 1.19 for every dollar invested company earns 0.19 cents; Capital recovery period is 5 years; Sensitivity analysis indicates that the project supports an increase in costs of 4% decrease in revenues and 3.37% lower one getting results therefore does not affect changes in project costs and revenues so the project is feasible, the conclusions and recommendations so determined, accompanied by the bibliography consulted with their respective annexes.